Factors affecting stress among UiTM Kampus Bandaraya Melaka students / Nur Aqilah Mastor - Mastor, Nur Aqilah (Faculty of Business and Management, 2020)
The main purpose of conducting this study is to examine the relationship between financial factor, relationship factor, academic factor and stress among UiTM Kampus Bandaraya, Melaka students. Total population for students of Human Resources Management in UiTM Kampus Bandaraya, Melaka is 475 students. Hence, a sample size consists of 200 students to distribute questionnaires. Convenience method has been used as sampling technique for the study. Questionnaire is the tool used by researcher to collect the data for this research. Data has been analysed through Statistical Packages for Social Sciences (SPSS). The Frequency Analysis, Reliability Analysis, Descriptive Statistics, Correlation and Multiple Regression analysis has been applied to identify the result of the study. The findings of this study have shown that there is a relationship between the financial factor, the relationship factor and the academic stress factor. Result of this study is helpful for students and academician of UiTM Kampus Bandaraya Melaka, so that they can get the better understanding about the relationship exist between financial factor, relationship factor, academic factor and stress as they can learn more on how to reduce their stress while study at universities.